Solutions of Domestic Violence Against Women: A Focus on Saudi Arabia: A Literature Review - Alghamdi, Jweriah (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
Abstract Domestic violence against women (DVAW) remains a persistent issue worldwide, surpassing cultural, religious, and socio-economic boundaries. While extensive research has examined this phenomenon globally, the scholarly literature on domestic violence in Saudi Arabia remains limited. Existing studies and international reports indicate that many Saudi women experience domestic violence in silence, often constrained by socio-cultural and legal barriers. This study examines the applicability of Australian policies and intervention strategies in addressing DVAW in Saudi Arabia and explores how Saudi Vision 2030 can serve as a catalyst for policy-driven reforms aimed at enhancing women's empowerment and Labor market participation. This research is grounded in feminist and human rights theoretical frameworks and employs a qualitative methodology based on thematic analysis of secondary data. The primary sources include reports from the Committee on the Elimination of Discrimination against Women (CEDAW), academic studies, Australian policy documents, and the Saudi Vision 2030 document. The analysis identifies three key policy interventions: (1) addressing socioeconomic inequality as a fundamental driver of domestic violence through primary prevention strategies; (2) developing inclusive policies that recognize the diverse experiences of women, including expatriates and individuals with disabilities; and (3) implementing a multi-sectoral response model that integrates government agencies, civil society organizations, and awareness campaigns to support victims effectively. The findings suggest that key elements of Australia’s DVAW policy framework can be adapted to the Saudi context, contributing to the advancement of women’s rights and improving their socio-economic status. This study underscores the importance of evidence-based policymaking and international best practices in shaping domestic violence prevention and response strategies within Saudi Arabia.